2012
DOI: 10.1007/s10886-012-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Mediated Effects of Glucosinolates on Different Natural Enemies of a Specialist Aphid

Abstract: The cabbage aphid Brevicoryne brassicae is a specialist herbivore that sequesters glucosinolates from its host plant as a defense against its predators. It is unknown to what extent parasitoids are affected by this sequestration. We investigated herbivore-mediated effects of glucosinolates on the parasitoid wasp Diaeretiella rapae and the predator Episyrphus balteatus. We reared B. brassicae on three ecotypes of Arabidopsis thaliana that differ in glucosinolate content and on one genetically transformed line w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 55 publications
4
65
0
Order By: Relevance
“…We found that D. rapae parasitoids had a significant preference for volatiles from aphid-infested Col-0 plants and ein2-1 mutants, which confirms previous findings that these parasitoids respond to volatile blends emitted by B. brassicae-infested A. thaliana plants (Kos et al, 2012 . This result on D. rapae development is consistent with our finding of D. rapae preference for plants simultaneously infested with aphids and caterpillars.…”
Section: Effects On Indirect Defensesupporting
confidence: 91%
“…We found that D. rapae parasitoids had a significant preference for volatiles from aphid-infested Col-0 plants and ein2-1 mutants, which confirms previous findings that these parasitoids respond to volatile blends emitted by B. brassicae-infested A. thaliana plants (Kos et al, 2012 . This result on D. rapae development is consistent with our finding of D. rapae preference for plants simultaneously infested with aphids and caterpillars.…”
Section: Effects On Indirect Defensesupporting
confidence: 91%
“…Interestingly, D. semiclausum showed a reversed preference to the host-infested plants at higher aphid density (Chapter 5). A positive correlation between preference behaviour and performance of parasitoids has been reported previously Kos et al, 2012). In this thesis, we also found that the parasitoid D. semiclausum preferred volatiles from plants that benefit their performance.…”
Section: Trade-off Between Plant Direct and Indirect Defencessupporting
confidence: 87%
“…Glucosinolates (GSLs) are amino acid-derived natural plant products in the Brassicaceae family, which are well known for their role as a degradation product that induces resistance against generalist herbivores (Kos et al, 2012) and microorganisms (Brader et al, 2006) in plants, as well as for their cancer-preventing properties in humans. In addition, GSLs have gained increasing significance as flavor compounds and potential biopesticides (Mithen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent GSL biosynthetic precursor amino acids include methionine, tryptophan, and phenylalanine, which result in aliphatic, indolic, and aromatic GSLs, respectively (Kos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%